Land Plots as a Variety of Immovable Things - ZOLOTAREVA, Alla Efratovna; STARODUMOVA, Svetlana Jurievna; NEZNAMOVA, Alla Andreevna; LENKOVSKAYA, Renata Romanovna; VOLKOVA, Maria Alexandrovna (Journal of Advanced Research in Law and Economics, 2017)
The article deals with attributes of immovable things, land plots in particular, as a special variety of an immovable thing. We have analyzed legal precedents, which allowed identifying various items of immovable property and relate them to each other. In our research, we used general scientific and law-specific methods of cognition: historical legal, formal legal, comparative legal, etc. We have found gaps in the land legislation and civil legislation related to incomplete definitions and lack of clearly described attributes of immovable things. We have accounted for the latest legislative changes characterizing judicial attribute of any immovable property. Based on the identified attributes, we divided real estate into groups and provided a definition for the concept of a land plot as a special variety of real estate, without which things cannot exist and may not be divided into movable and immovable.